2021
DOI: 10.3390/ijgi10050316
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Laser Scanner and Photogrammetry for Heritage BIM Enhancement

Abstract: Digital 3D capture and reliable reproduction of architectural features is the first and most difficult step towards defining a heritage BIM. Three-dimensional digital survey technologies, such as TLS and photogrammetry, enable experts to scan buildings with a new level of detail. Challenges in the tracing of parametric objects in a TLS point cloud include the reconstruction of occluded parts, measurement of uncertainties relevant to surface reflectivity, and edge detection and location. In addition to image-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 58 publications
0
51
0
2
Order By: Relevance
“…Laser Scanning and IBM satisfy the 3D modeling needs for inspection, multitemporal deformation monitoring, numerical modeling, and building information modeling (BIM) [315,316], and enable surface feature extraction regarding deterioration and physical defects. The integration between them emphasizes the complementarity of geometric and color information.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…Laser Scanning and IBM satisfy the 3D modeling needs for inspection, multitemporal deformation monitoring, numerical modeling, and building information modeling (BIM) [315,316], and enable surface feature extraction regarding deterioration and physical defects. The integration between them emphasizes the complementarity of geometric and color information.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…Several papers discuss about the application of BIM to heritage and according to M. Castellan-Román and F. Pinto-Puerto, three focuses can be identified in relation with HBIM: modelling of historical buildings as a particular case, high geometric accuracy modelling, and analysis and generation of knowledge [53]. In the last years, different articles highlight the potential and application of HBIM mainly used for built heritage but also for movable heritage inside it [54][55][56][57][58]. Other authors, while understanding the impact of HBIM, also mention that this tool does not offer a significative improvement in the field of dissemination of cultural heritage [59].…”
Section: Trends and Reflections On Immovable Cultural Heritage Data B...mentioning
confidence: 99%
“…In this context, several studies have shown how digital models, related information, schedules and databases can be shared through digital twins, favouring information sharing and minimising data loss [35][36][37][38][39][40].…”
Section: Introduction: the Digital Era In Cultural Heritagementioning
confidence: 99%